2018
DOI: 10.1007/s00436-018-5807-9
|View full text |Cite
|
Sign up to set email alerts
|

Human cystic echinococcosis in Turkey: a preliminary study on DNA polymorphisms of hydatid cysts removed from confirmed patients

Abstract: Cystic echinococcosis caused by the larval stages of Echinococcus granulosus sensu lato s.l is endemic in Turkey with a high public health impact particularly in rural areas. The aim of this study was to investigate the genetic variation and population structure of E. granulosus s.s using metacestode isolates removed from surgically confirmed patients originating from several regions in Turkey and to investigate the occurrence of autochthonous transmission. Using DNA extracted from a total of 46 human-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In the recent study, E. canadensis (G6 genotype) was reported in sheep from Elazığ (Mehmood S et al 2020) As a result of the analyses, it has been observed that sheep and cattle have the same haplotypes with humans. This result revealed the importance of sheep and cattle in autochthonous transmission (Orsten et al 2018). Consistent with this assessment, some haplotypes were found to be common for humanand cattle-derived isolates in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the recent study, E. canadensis (G6 genotype) was reported in sheep from Elazığ (Mehmood S et al 2020) As a result of the analyses, it has been observed that sheep and cattle have the same haplotypes with humans. This result revealed the importance of sheep and cattle in autochthonous transmission (Orsten et al 2018). Consistent with this assessment, some haplotypes were found to be common for humanand cattle-derived isolates in this study.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, all the isolates collected in this study were confirmed by BLAST algorithm as E. granulosus s.l. From Turkey, there are several reports on molecular characterization of E. granulosus s.l isolates from various intermediate hosts (Schneider et al 2008;Utuk et al 2008;Snabel et al 2009;Ergin et al 2010;Simsek et al 2011;Utuk and Simsek 2013;Bakal et al 2015;Eroglu et al 2016;Orsten et al 2018;Kurt et al 2020;Örsten et al 2020). These studies showed that E. granulosus s.s. (genotypes G1-G3) is the predominant species obtained from hydatid materials in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of research conducted on molecular identification of E. granulosus s.l. isolates from sheep, cattle, goats and humans from different regions of Turkey (Schneider et al ., 2010; Utuk et al ., 2008; Šnàbel et al ., 2009; Ergin et al ., 2010; Simsek et al ., 2011; Eryildiz and Şakru, 2012; Bakal et al ., 2015; Eroğlu et al ., 2016; Orsten et al ., 2018). According to these studies, E. granulosus s.s. (G1–G3 genotypes) was the most common species causing CE in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers indicated that G1 and G3 genotypes ( E. granulosus s.s. ) are predominant in the human host in Turkey (Utuk et al ., 2008; Snabel et al ., 2009; Ergin et al ., 2010; Simsek et al ., 2011; Eryıldız and Şakru, 2012; Bakal et al ., 2015; Eroğlu et al ., 2016; Erdoğan et al ., 2017; Oral Babaoğlu et al ., 2018; Orsten et al ., 2018). Echinococcus canadensis (G7 genotype), also known as pig strain, was reported from Turkey for the first time by Snabel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of humans to E. granulosus is common due to the lifestyle of the prople who live in close proximity to sheep and dogs. The disease is often seen in women aged between 30 and 50 years who are more likely to be in contact with animals in rural areas (Orsten et al, 2018, Yolasigmaz et al, 2006) such as the chosen districts of Izmir province. Most people live in rural areas and are engaged in animal husbandry in this area.…”
Section: Introductionmentioning
confidence: 99%